(untitled) (Journal of Science and Technology, 2025)
Bullying is a social problem that not only physically and psychologically affects victims but also disrupts the process of teaching and learning in senior high schools (SHS). We used an exploratory sequential mixed-method design comprising a survey and a double-blinded experiment to study the role of dominance hierarchy as the primary mechanism of bullying to effectively design anti-bullying strategies. The sample size used in the survey to validate the influence of dominance hierarchical structures on bullying was 79 students, while the experimental design to causally link dominance hierarchy to bullying included a sample of 21 students. The dominance hierarchy is one in which bullying behavior is exhibited as a means to rise up a social hierarchy. The current study validated that the dominance hierarchy is the more prevalent form of bullying in Ghana. We also observed that while bullying behavior sharply increases in SHS 3, bullying victimization does the opposite. This allows us to implement anti-bullying strategies for the most affected groups. Finally, the highest percentage of bullied individuals in SHS 1 are those who have a high social status relative to their peers, and the students who bully most frequently in SHS 3 are those who have a lower social status in school compared to their peers. Flattening the hierarchy is an effective way to significantly decrease bullying behavior. Therefore, measures such as increasing senior-junior cooperation through leadership positions, which are largely absent in SHS, will be effective at substantially decreasing bullying behavior in our schools.